Antiferromagnetic topological insulator MnBi2Te4: synthesis and magnetic properties. Issue 2 (16th December 2019) - Li, Hao; Liu, Shengsheng; Liu, Chang; Zhang, Jinsong; Xu, Yong; Yu, Rong; Wu, Yang; Zhang, Yuegang; Fan, Shoushan
Abstract : The synthesis of high quality MnBi2 Te4 crystals as the first intrinsic antiferromagnetic topological insulator to unearth exotic topological quantum phenomena. Abstract : Recently, MnBi2 Te4 has been discovered as the first intrinsic antiferromagnetic topological insulator (AFM TI), and it will become a promising material to discover exotic topological quantum phenomena. In this work, we have realized the successful synthesis of high-quality MnBi2 Te4 single crystals by solid-state reactions. The as-grown MnBi2 Te4 single crystal exhibits a van der Waals layered structure, which is composed of septuple Te–Bi–Te–Mn–Te–Bi–Te sequences as determined by X-ray diffraction and high-resolution high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM). The magnetic order below 25 K as a consequence of A-type antiferromagnetic interaction between Mn layers in the MnBi2 Te4 crystal suggests the unique interplay between antiferromagnetism and topological quantum states. Moreover, the transport measurements of MnBi2 Te4 single crystals further confirm its magnetic transition. This study on the first AFM TI of MnBi2 Te4 will guide the future research on other potential candidates in the MBi x Te y family (M = Ni, V, Ti, etc. ).